Chapter 5.10 Development of RMA in China - Fang Xu; Wenjie Lu (Emerald Publishing Limited, 2023)
With the government's increased investment in sci-tech and the requirement of scientific research management, RMAs have gradually flourished in China after the 1980s. However, there is no professional qualification specifically for RMA in China and RMA professionals are from various departments. With the arrival of the 21st century, the rapid development of sci-tech has led to the strengthening of the position and role of RMA in research activities. The profession of RMA has made great progress, and a professional contingent of RMA has gradually been formed. This chapter will review the history and development of RMAs in China. Specifically, it includes the evolutionary history of China's sci-tech policy, how RMAs developed as a profession, current state of RMAs, the size and nature of the RMA profession (taking the academic community CASSSP as an example), and future trends of RMAs in China.
10.1108/978-1-80382-701-820231043; 10.1108/978-1-80382-701-820231043; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262